2003
DOI: 10.1089/105072503322238818
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Secondary Hypothyroidism Due to a Mutation C105Vfs114X Thyrotropin-β Mutation: Genetic Study of Five Unrelated Families from Switzerland and Argentina

Abstract: We identified five patients with congenital secondary hypothyroidism with isolated thyrotropin (TSH) deficiency originating from three and two unrelated Argentinean and Swiss families, respectively. The affected patients presented with both low TSH as well as low thyroid hormone levels. Further, TSH-releasing hormone (TRH) stimulation failed to increase serum TSH, whereas prolactin increased adequately. These affected children were homozygous for a 1-bp deletion (822delT) in the TSH-beta subunit gene leading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
4
27
0
Order By: Relevance
“…Of these, C105Vfs114X is the most frequently reported mutation in the TSH␤ gene, accounting for more than half of all published cases to date (17). Whereas the occurrence of this mutation in three German families seems to be due to a founder effect (15), other families do not share a common haplotype, suggesting that codon 105 is a mutational hotspot (17). We previously identified a sixth homozygous TSH␤ mutation in a 4-month old girl of Turkish origin (23).…”
Section: Ongenital Secondary (Central) Hypothy-mentioning
confidence: 98%
See 1 more Smart Citation
“…Of these, C105Vfs114X is the most frequently reported mutation in the TSH␤ gene, accounting for more than half of all published cases to date (17). Whereas the occurrence of this mutation in three German families seems to be due to a founder effect (15), other families do not share a common haplotype, suggesting that codon 105 is a mutational hotspot (17). We previously identified a sixth homozygous TSH␤ mutation in a 4-month old girl of Turkish origin (23).…”
Section: Ongenital Secondary (Central) Hypothy-mentioning
confidence: 98%
“…After cloning of the gene in 1988 (6 -8), five different homozygous TSH␤ mutations leading to congenital secondary hypothyroidism have been identified in the coding region of the gene: G29R (9, 10), C105Vfs114X (11)(12)(13)(14)(15)(16)(17)(18), E12X (19), Q49X (20 -22), and C85R (22). Of these, C105Vfs114X is the most frequently reported mutation in the TSH␤ gene, accounting for more than half of all published cases to date (17). Whereas the occurrence of this mutation in three German families seems to be due to a founder effect (15), other families do not share a common haplotype, suggesting that codon 105 is a mutational hotspot (17).…”
Section: Ongenital Secondary (Central) Hypothy-mentioning
confidence: 99%
“…Congenital isolated thyrotropin (TSH) deficiency is an unusual condition, with a prevalence from 1/30,000 to 1/50,000 newborns, characterized by low levels of both thyroid hormones and TSH and usually presenting early typical signs of severe hypothyroidism [1, 2, 3, 4, 5, 6, 7, 8, 9, 10]. Patients with this disorder are not detected by neonatal screening programs based on TSH measurements, which is frequently in the low to normal range.…”
Section: Introductionmentioning
confidence: 99%
“…Five different β-TSH mutations have been described so far: (1) a missense G29R mutation in exon 2, in 5 Japanese consanguineous families [12], (2) a nonsense mutation at codon 12 (E12X) in exon 2, in 2 consanguineous Greek families [4], (3) a nonsense mutation at codon 49 (Q49X) in exon 2, in an Egyptian consanguineous patient [3]and in 2 consanguineous Turkish siblings [5], (4) a mutation in the donor splice site of intron 2 of the β-TSH gene (IVS2 +5; G>A), in a consanguineous German family [6], and (5) a single base pair deletion in exon 3 (822delT) resulting in the substitution of cysteine 105 for valine and a frameshift with the appearance of a premature stop codon at position 114 (C105fs114X). This last mutation is the most frequently reported, is less geographically restricted and has been described in 2 consanguineous Brazilian families [2], 1 Belgian family [7], 3 unrelated German families with 5 affected individuals [8, 9], 2 brothers from the USA [13]and in 2 unrelated Swiss families [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, in a study of patients with isolated CH-C from European countries [17,18] it was found that the mutation 313 delT (p.C105Vfs114X) is the most frequent cause of the TSHβ-subunit gene defects in western and central Europe as well as in Latin America. Interestingly, in eight patients with CH-C from seven unrelated Argentinean families, the same mutation (p.C105Vfs114X) was identified [19].…”
Section: Central Hypothyroidism In the Context Of Multiple Pituitary mentioning
confidence: 99%